Trauma-Informed Care in Anesthesia for Women with a History of Sexual Assault: Investigating Provider Perceptions - Rose Peterson, Scotti; Edward Nguyen, The-Hung; Rollison, Sarah (AANA journal, 2025)
According to the Centers for Disease Control and Prevention, one in four women in the United States has experienced attempted or completed rape, and over half have experienced a form of sexual violence in their lifetime. Despite this prevalence, there is currently no formal position statement regarding the role of trauma-informed care (TIC) in anesthesia. This study investigates provider knowledge and attitudes regarding TIC principles and specific applications to perioperative practices during the care of female-identifying patients. Interactive educational presentations were provided to perioperative staff in surgical centers across a large academic medical center in the Mid-Atlantic United States. Pre-post education surveys measured participant knowledge, attitudes, and practices surrounding TIC on a four-point Likert scale. Data were numerically coded and evaluated using independent t-test analysis. Results demonstrate that providers vastly underestimate the prevalence of sexual assault, do not regularly integrate TIC principles, desire additional TIC education, and are individually motivated to modify practices. Integrating universal TIC guidelines into the anesthesia care of this patient population can serve as a bridge to formal protocols, provider education, and practice integration.